The measurement of adult blood pressure and management of hypertension before elective surgery: Joint Guidelines from the Association of Anaesthetists of Great Britain and Ireland and the British Hypertension Society. (17th January 2016) - Hartle, A.; McCormack, T.; Carlisle, J.; Anderson, S.; Pichel, A.; Beckett, N.; Woodcock, T.; Heagerty, A.
Summary: This guideline aims to ensure that patients admitted to hospital for elective surgery are known to have blood pressures below 160 mmHg systolic and 100 mmHg diastolic in primary care. The objective for primary care is to fulfil this criterion before referral to secondary care for elective surgery. The objective for secondary care is to avoid spurious hypertensive measurements. Secondary care should not attempt to diagnose hypertension in patients who are normotensive in primary care. Patients who present to pre‐operative assessment clinics without documented primary care blood pressures should proceed to elective surgery if clinic blood pressures are below 180 mmHg systolic and 110 mmHg diastolic.